Erythritol-Enriched Air-Polishing Powder for the Surgical Treatment of Peri-Implantitis - Silvio Taschieri; Roberto Weinstein; Massimo Del Fabbro; Stefano Corbella (The Scientific World Journal)
Peri-implantitis represents a major complication that can compromise the success and survival of implant-supported rehabilitations. Both surgical and nonsurgical treatment protocols were proposed to improve clinical parameters and to treat implants affected by peri-implantitis. A systematic review of the literature was performed on electronic databases. The use of air-polishing powder in surgical treatment of peri-implantitis was investigated. A total of five articles, of different study designs, were included in the review. A meta-analysis could not be performed. The data from included studies reported a substantial benefit of the use of air-polishing powders for the decontamination of implant surface in surgical protocols. A case report of guided bone regeneration in sites with implants affected by peri-implantitis was presented. Surgical treatment of peri-implantitis, though demanding and not supported by a wide scientific literature, could be considered a viable treatment option if an adequate decontamination of infected surfaces could be obtained.